Effects of multiphase turbulence on the flow and hazard behavior of dilute pyroclastic density currents : a thesis submitted in partial fulfilment for the degree of Doctor of Philosophy in Earth Science at Massey University, Palmerston North, New Zealand - Uhle, Daniel Holger (Massey University, 2024)
Pyroclastic surges (also dilute pyroclastic density currents or dilute PDCs) are amongst the most hazardous volcanic phenomena associated with explosive volcanic eruptions and hydrothermal explosions. These fast-moving, turbulent, polydisperse multiphase flows of hot volcanic particles and gas occur frequently and have severe impacts on life and infrastructure. This is attributed to a compounding of hazard effects: large flow-internal dynamic pressures of tens to hundreds of kilopascals destroy reinforced buildings and forests; temperatures of up to several hundreds of degrees Celsius pose severe burn hazards; and readily respirable hot fine ash particles suspended inside dilute PDCs cause rapid asphyxiation. Direct measurements inside pyroclastic density currents are largely absent, and previous research has used a combination of detailed field studies on PDC deposits, laboratory experiments on analog density currents, numerical modeling, and theoretical work to interrogate the internal flow structure, gas-particle transport, sedimentation and destructiveness of dilute PDCs. Despite major scientific advances over the last two decades, significant fundamental gaps in understanding the turbulent multiphase flow behavior of dilute PDCs endure, preventing the development of robust volcanic hazard models that can be deployed confidently. Critical unknowns remain regarding: (i) how turbulence is generated in dilute PDCs; (ii) how multiphase processes modify the flow and turbulence structure of dilute PDCs; and (iii) if and how turbulent gas-particle feedback mechanisms affect their destructiveness. To address these gaps in understanding, this PhD research involved high-resolution measurements of velocity, dynamic pressure, particle concentration, and temperature inside large-scale experimental dilute PDCs. It is shown that dilute PDCs are characterized by a wide turbulence spectrum of damage-causing dynamic pressure. This spectrum is strongly skewed towards large dynamic pressures with peak pressures that exceed bulk flow values, routinely used for hazard assessments, by one order of magnitude. To prevent severe underestimation of the damage potential of dilute PDCs, the experimentally determined ratio of turbulence-enforced pressure maxima and routinely estimated bulk pressures should be used as a safety factor in hazard assessments. High-resolution measurements of dynamic pressure and Eulerian-Lagrangian multiphase simulations reveal that these pressure maxima are attributed to the clustering of particles with critical particle Stokes numbers (𝑆𝑡=𝒪(1)) at the margins of coherent turbulence structures. The characteristic length scale and frequency of coherent structures modified in this way are controlled by the availability of the largest particles with critical Stokes number. Through this, spatiotemporal variations in peak pressures are governed by the mass loading and subsequent sedimentation of these clustered particles. In addition to the ‘continuum phase’ loading pressure, the measurements also revealed that the direct impact of clustered margins and high Stokes number particles decoupling from margins with structures generate instantaneous impacts. These piercing-like impact pressures exceed bulk pressure values by two orders of magnitude. Particle impact pressures can cause severe injuries and damage structures. They can be identified as pockmarks on buildings and trees after eruptions. This new type of PDC hazard and the magnitude of pressure impacts need to be accounted for in hazard assessments. Systematic measurements of the evolving experimental pyroclastic surges along the flow runout demonstrate that time-averaged vertical profiles of all flow velocity components and flow density obey self-similar distributions. Variations of the roughness of the lower flow boundary, geometrically scaling ash- to boulder-sized natural substrates, showed the self-similar distributions are independent of the roughness. Mathematical relationships developed from the self-similar velocity and density distribution reveal the self-similar vertical distribution of mean dynamic pressure. This empirical model can inform multi-layer PDC models and estimate the height and values of peak time-averaged dynamic pressure for dilute PDCs of arbitrary scale. Turbulence fluctuations around the mean were investigated through Reynolds decomposition. The large-scale turbulence structure and the dominant source of turbulence generation are shown to be controlled by free shear with the outer flow boundary, while strong density gradients at the basal high-shear flow boundary dampen turbulence generation. The large-scale, shear-induced coherent turbulence structures can be tracked along the runout and were found to be superimposed by smaller turbulence structures. In Fourier spectra of dynamic pressure, flow velocity, and temperature, these sub-structures are observed as discrete frequency bands that correspond to the coarse modes of the spatiotemporally evolving flow grain-size distributions. This can be associated with the preferential clustering of particles at the peripheries of the sub-structures. Following the decoupling of particle clusters, the rapid sedimentation of particle clusters occurs periodically at the characteristic frequency of the turbulence sub-structures. This mechanism of preferential clustering, decoupling and rapid sedimentation of particles with critical particle Stokes numbers is an important mechanism of turbulent sedimentation to explain the spatiotemporally evolving flow grain-size distribution of pyroclastic surges.
Keywords: Volcanism; Mathematical models; Volcanological research; Volcanic ash, tuff, etc.; Volcanic eruptions; pyroclastic density currents; turbulence; natural hazard; volcanology; earth science; multiphase physics; fluid dynamics; experimental eruptions; 370512 Volcanology